TINJAUAN YURIDIS PERLINDUNGAN HUKUM ANAK YANG TERLIBAT TINDAK PIDANA NARKOTIKA - Gilang Khassandra (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT Drug abuse is an act that seems to be commonplace in Indonesia. The misuse of narcotics contains the intention of a person who without right or against the law uses narcotics. That is, if a person who does not have a permit or authority uses narcotics either for himself or for others, it can be categorized as abuse.Protection of criminal law for children who are involved in narcotics crime is by using diversion through a restorative justice approach. According to the above provisions, a child who commits a criminal act and is processed in juvenile justice has rights guaranteed by the Law on the Juvenile Criminal Justice System. One of these is the right not to be arrested, detained and imprisoned except as a last resort.Obstacles in providing legal protection for children involved in narcotics crime can be seen through the legal system consisting of legal structure, legal substance and legal culture as well as through law enforcement factors consisting of law enforcement, laws, facilities or facilities, society and culture. Keywords: Legal protection. Son Narcotics Crimes.